2019
DOI: 10.3389/fimmu.2019.00867
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab and Bevacizumab Attenuate Cisplatin Resistant Ovarian Cancer Cells Progression Synergistically via Suppressing Epithelial-Mesenchymal Transition

Abstract: The AURELIA trial demonstrated that adding Bevacizumab to chemotherapy significantly improved progression-free survival (PFS) for platinum resistant recurrent ovarian cancer. Recently, immunotherapy also presented potential anti-tumor effects in several malignant solid tumors. This study aimed to investigate whether combining anti-PD-L1 Atezolizumab with BEV may have a synergistic effect and enhance the efficacy of both treatments in cisplatin resistant epithelial ovarian cancer (CREOC). We retrospectively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
1
40
0
1
Order By: Relevance
“…Notably, anti-VEGF treatment suppressed PD-L1 expression and EMT via decreased STAT3 phosphorylation in cisplatin resistant ovarian cancer cells. Moreover, anti-VEGF and anti-PD-L1 agents acted synergistically to reduce tumor growth in vivo, which might have been due to enhancement of the immunotherapy efficacy by the anti-EMT effect of the anti-VEGF treatment [166].…”
Section: Emt and Immunotherapy Resistancementioning
confidence: 99%
“…Notably, anti-VEGF treatment suppressed PD-L1 expression and EMT via decreased STAT3 phosphorylation in cisplatin resistant ovarian cancer cells. Moreover, anti-VEGF and anti-PD-L1 agents acted synergistically to reduce tumor growth in vivo, which might have been due to enhancement of the immunotherapy efficacy by the anti-EMT effect of the anti-VEGF treatment [166].…”
Section: Emt and Immunotherapy Resistancementioning
confidence: 99%
“…In addition, the authors discovered that atezolizumab and bevacizumab in combination substantially inhibited cisplatin-resistant ovarian cancer cell proliferation, migration and invasion, which they attributed to the impediment of EMT through the signal transducer and activator of transcription 3 (STAT3) pathway. Finally, an in vivo mouse model demonstrated synergistic reduction in tumor burden in the mice treated with atezolizumab and bevacizumab compared to either monotherapy alone [ 21 ]. While these results appear promising and suggest non-immune mediated effects of PD-1-based treatments, as this study was not performed in an immunocompetent model, a deficiency remains in our understanding of how these therapies act in concert to promote anti-tumor immunity.…”
Section: Pd-1 Based Combinatorial Approachesmentioning
confidence: 99%
“…These results indicate that PD-1 therapy alone will not be efficacious enough to improve survival for EOC patients. However, evidence is emerging that combinatorial methods will be critical to optimizing EOC patient response to immunotherapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor-A (VEGF-A), one of the most important angiogenic factors (1-3), has been reported to effect cancer growth and development (3)(4)(5)(6). VEGF-A is also involved in the regulation of immune response in various cancers (3,(7)(8)(9)(10)(11)(12)(13)(14). Recent reports have indicated that anti-VEGF therapy has the important effect of enhancing anti-tumor immunity in various cancers (3,(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…VEGF-A is also involved in the regulation of immune response in various cancers (3,(7)(8)(9)(10)(11)(12)(13)(14). Recent reports have indicated that anti-VEGF therapy has the important effect of enhancing anti-tumor immunity in various cancers (3,(7)(8)(9)(10)(11)(12)(13)(14). The immune system affects tumor progression and dissemination, and treatment response (15)(16)(17)(18).…”
mentioning
confidence: 99%